Effect of a Freeze-Thaw Cycle on Properties of Microsomal Membranes from Wheat - Borochov, Amihud (1987)
A freeze-thaw cycle to −12°C induced several physical and compositional changes in the microsomal membranes isolated from crown tissue of winter wheat (Triticum aestivum L. cv Frederick). Exposing 7-day-old, nonacclimated seedlings to a single freeze-thaw cycle prevented regrowth of the crown and resulted in increased membrane semipermeability. The phospholipid and protein content of microsomal membranes isolated from the crowns decreased by 70 and 50%, respectively. Microsomal membranes isolated after the lethal freeze-thaw stress, and liposomes prepared from total membrane lipids, exhibited greater microviscosity, measured by fluorescence polarization of 1,6-diphenyl-1,3,5-hexatriene. The number of free thiol groups per milligram membrane protein, measured using the specific fluorescent probe, N-dansylaziridine, decreased after freezing. In contrast, acclimated wheat seedlings which showed increased freezing tolerance, as indicated by survival and ion leakage, suffered almost no effects from the freeze thaw treatment as determined by measurements of membrane microviscosity, phospholipid content, protein content, or danzylaziridine fluorescence. An examination of membranes isolated from frozen tissue showed that most of the changes occurred during the freezing and not during the thawing phase.